Athletic supplements: Creatine - Chiang, R. (1998)
Creatine monohydrate appears to be an effective supplement for those seeking to make gains in muscle strength and size through weight training. Also, it may benefit athletes involved in sports that call upon short term, high intensity movements such as the shot put or the 100 m run. Vegetarians or those whose diets consist of little meat are likely to benefit from creatine supplementation as well. However, those who initially have higher levels of creatine in their bodies to will notice less improvement than those with lower initial levels (such as the vegetarians). Also, creatine supplementation has not been shown to improve performance in longdistance / endurance type sports such cross country running or skiing. Athletes involved in such sports should be leery of possible weight gain. Little is known as to whether creatine supplements can improve performance in sports such as basketball or wrestling that mix endurance-type activities and "power" movements. This probably depends on the specific sport and the individual athlete (for instance, it can depend on what the strength and weaknesses of the athlete are in his/her respective sport).